2022
DOI: 10.1002/jso.26914
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative pectoral block versus thoracic paravertebral block for postoperative analgesia after breast cancer surgery: A randomized controlled trial

Abstract: Background and Methods With the increasing rate of breast cancer surgery, the pain management of these patients gains importance. The aim of this study is to compare the ultrasound (US) guided thoracic paravertebral block (TPV) versus intraoperative pectoral nerve block (PECS) with a low volume local anaesthetic for postoperative analgesia after breast cancer surgery. A total of 41 patients underwent mastectomy and sentinel lymph node biopsy or modified radical mastectomy were included in this randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…We noted that this additional analgesic dose in the Kulhari et al study actually is the total intravenous mg morphine consumption for postoperative pain control in 24 h and a 30% expected between-group difference is used for sample size calculation. In the study of Sagun et al, 1 however, additional analgesics were intravenous mg nonsteroid anti-inflammatory drug and meperidine. Furthermore, this study compared the between-group differences in total mg doses of additional analgesic drugs in the first 48 h postoperatively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We noted that this additional analgesic dose in the Kulhari et al study actually is the total intravenous mg morphine consumption for postoperative pain control in 24 h and a 30% expected between-group difference is used for sample size calculation. In the study of Sagun et al, 1 however, additional analgesics were intravenous mg nonsteroid anti-inflammatory drug and meperidine. Furthermore, this study compared the between-group differences in total mg doses of additional analgesic drugs in the first 48 h postoperatively.…”
mentioning
confidence: 99%
“…To the Editor, In a prospective, randomized single-blind clinical study with a small sample size including 41 patients who underwent mastectomy and sentinel lymph node biopsy or modified radical mastectomy, Sagun et al 1 compared postoperative analgesic efficacy of pectoral block and thoracic paravertebral block. They showed that the two blocks were comparable with respect to postoperative analgesia and additional analgesic requirements.…”
mentioning
confidence: 99%